2021
DOI: 10.1039/d0ra08571e
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral metallofullerene electrides of Ca12O12 with remarkable nonlinear optical response

Abstract: Electride formation by alkali metal doping with a drastic increase in hyperpolarizability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 67 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…The excess electrons of alkali metals have caused reduction in energy gaps of these complexes. The highest NLO response of the order of 1.0 × 10 6 au was obtained for endohedral electrides (endo-K@Ca 12 O 12 ) (Ahsan et al, 2021).…”
Section: Alkali Metal Doped Nanocagesmentioning
confidence: 97%
See 1 more Smart Citation
“…The excess electrons of alkali metals have caused reduction in energy gaps of these complexes. The highest NLO response of the order of 1.0 × 10 6 au was obtained for endohedral electrides (endo-K@Ca 12 O 12 ) (Ahsan et al, 2021).…”
Section: Alkali Metal Doped Nanocagesmentioning
confidence: 97%
“…Many organic and inorganic excess electron based NLO materials have been designed theoretically. Doping is an efficient approach to enhance the NLO response of various systems including cyclacene (Xu et al, 2009), calix [4] pyrrole (W. Chen et al, 2006), organic and inorganic fullerenes (Ahsan et al, 2021;Liu et al, 2019;Shakerzadeh et al, 2016a;Ullah et al, 2020b), phosphorenes, B 10 H 14 baskets (Muhammad et al, 2009), cyclic polyamines (Li et al, 2009a), fluorocarbons (H. L. Xu et al, 2007), and so forth.…”
Section: Excess Electron Based Systems In Nonlinear Opticsmentioning
confidence: 99%
“…A series of superalkali compounds with electride and alkalide characteristics have also been reported. 6–18 Thus, can a superalkali complex act as a switch as noted above? In 2015, Xu et al 18 studied the intermolecular interactions and NLO properties of a parallel stacked phenalenyl radical and Li 3 ring (parallel Li 3 –PHY).…”
Section: Introductionmentioning
confidence: 99%
“…5 Also, many alkalides and electrides have been suggested to serve as nonlinear optics (NLO) materials. 6–18 Since Dye et al 19,20 reported their pioneering work on the electride of Cs + (18-crown-6)e − and the alkalide of Na + (cryptand-[2.2.2])Na − , a great deal of work has been done to discover and characterize the varieties of alkalides and electrides. 6–18,21–23…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the most attractive nanocages with the general formula X12Y12 are the most stable nanocages. Because of unique applications of fullerene-like structures in electronic devices, imaging materials, magnetic recording and environmental processes, investigating of them is one of the most important topics in nanotechnology [6][7][8][9][10][11][12]. Theoretical studies have confirmed that the X12Y12 clusters have two structures including a cubic quasi-structure consisting of square and hexagonal rings, and a quasi-fullerene structure having pentagonal and hexagonal rings.…”
Section: Introductionmentioning
confidence: 99%